A comparative study of thick TiSiCN nanocomposite coatings deposited by dcMS and HiPIMS with and without PEMS assistance - Lin, Jianliang; Wei, Ronghua (Surface & coatings technology, 2018)
As one version of high power impulse magnetron sputtering (HiPIMS) technique, deep oscillation magnetron sputtering (DOMS) generates large oscillation high power pulses to achieve a high fraction of metallic ions of the target species for arc-free reactive HiPIMS sputtering. Plasma enhanced magnetron sputtering (PEMS), an advanced version of conventional dc magnetron sputtering (dcMS), generates an extremely high flux of low energy gas ions with hot filament thermionic emission to produce an extra global plasma in the deposition system. As compared to conventional dcMS, both DOMS and PEMS aim at utilizing a highly ionized plasma to improve the structure and properties of the coatings. To gain a better understanding of the advantages and limits of these techniques, we present a comparative study for the thick TiSiCN nanocomposite coatings (15 μm) deposited using dcMS and DOMS with and without the PEMS assistance. The time averaged ion energy distributions of the plasmas generated by these techniques for TiSiCN coating depositions were characterized using an electrostatic quadrupole plasma mass spectrometer (EQP). The microstructure and mechanical properties of the coatings were characterized using X-ray diffraction, scanning electron microscopy, scratch test and nanoindentation. The microstructure, residual stress, and mechanical properties of the coatings were linked to the plasma properties and discussed in details. It is clear that the PEMS assistance significantly improves the microstructure and mechanical properties of the coatings produced by either dcMS or DOMS along with residual stress reduction. •Higher metal ion fluxes (multiply charged) were observed in the DOMS plasma than the dcMS plasma.•The PEMS assistance generates a tremendous number of low energy gas ions by electron impact ionization.•Stress relaxation of thick TiSiCN coatings deposited by PEMS assistance.•The PEMS technique can be used to assist different sputtering techniques for achievingextreme 'energy flux' deposition.